DETERMINAN LIKUIDITAS DAN SOLVABILITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR TELEKOMUNIKASI DI BURSA EFEK INDONESIA - Milati, Nela Aini; Hartoto, Witjaksono Eko; santoso, aprih (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
Abstract. This study aims to analyze the effect of liquidity and solvency on the financial performance of telecommunications companies listed on the Indonesia Stock Exchange (IDX). The data used are secondary data obtained from the Indonesia Stock Exchange website for telecommunications companies from 2019 to 2023. The data were analyzed using multiple linear regression analysis. The results show that the current ratio has a negative and significant effect on return on assets, while the debt-to-equity ratio and debt-to-asset ratio have no effect on return on assets. Keyword: Current Ratio, Debt to Equity Ratio, Debt to Asset Ratio, dan Return on Asset.